The effect of perinatal interventions on parent anxiety, infant socio‐emotional development and parent‐infant relationship outcomes: A systematic review - Celia G. Smith; Emily J. H. Jones; Sam V. Wass; Dean Jacobs; Cassie Fitzpatrick; Tony Charman (Wiley, 2022)
Abstract Background Infants of parents with perinatal anxiety are at elevated likelihood of experiencing disruption in the parent‐infant relationship, as well as difficulties with socio‐emotional functioning in later development. Interventions delivered in the perinatal period have the potential to protect the early dyadic relationship and support infants' ongoing development and socio‐emotional outcomes. This review primarily aimed to examine the efficacy of perinatal interventions on parent anxiety, infant socio‐emotional development/temperament, and parent‐infant relationship outcomes. Secondarily, the review sought to understand how interventions focused principally on one member of the dyad affected the outcomes of the other, and which intervention components were common to successful interventions. Method Five electronic databases as well as manual search procedures were used to identify randomised controlled trials according to a PICO eligibility criteria framework. Risk of bias assessments were undertaken, and a narrative synthesis was conducted. The review was pre‐registered on PROSPERO (CRD42021254799). Results Twelve studies were analysed in total, including five interventions focused on the adult, and seven interventions focused on the infant, or the infant's relationship with their parent. Interventions incorporating cognitive behavioural strategies for affective disorders showed reductions in parent anxiety (N = 3), and interventions focusing on altering distorted maternal internal representations showed positive change in parent‐child dyadic interactions, and infant outcomes (N = 2). Evidence that interventions focused on one partner of the dyad led to improved outcomes for the other partner was limited. However, evidence was of mixed methodological quality. Conclusions It is important to integrate both parents and infants into treatment programmes for perinatal anxiety. Implications for clinical practice and future intervention trials are discussed.